2018
DOI: 10.1111/cas.13589
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐epidermal growth factor receptor therapy concurrently with induction chemotherapy in locoregionally advanced nasopharyngeal carcinoma

Abstract: Little is known about the efficacy and toxicity of anti‐epidermal growth factor receptor therapy concurrently with induction chemotherapy (IC) in locoregionally advanced nasopharyngeal carcinoma (LA‐NPC). The present study aimed to address this question. We identified 2848 patients with newly diagnosed LA‐NPC receiving IC between January 2012 and May 2015. The propensity score matching (PSM) method was used to balance various factors and to match patients. Survival outcomes and toxicities between different gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Cetuximab (CTX) and nimotuzumab (NTZ) are two major anti‐EGFR mAbs that have frequently been used for the treatment of NPC. Several studies have indicated that treatment with CTX or NTZ enhances the efficacy of chemoradiotherapy for locoregionally advanced NPC . However, the antitumor activity of anti‐EGFR mAbs for RM‐NPC has rarely been reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetuximab (CTX) and nimotuzumab (NTZ) are two major anti‐EGFR mAbs that have frequently been used for the treatment of NPC. Several studies have indicated that treatment with CTX or NTZ enhances the efficacy of chemoradiotherapy for locoregionally advanced NPC . However, the antitumor activity of anti‐EGFR mAbs for RM‐NPC has rarely been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that treatment with CTX or NTZ enhances the efficacy of chemoradiotherapy for locoregionally advanced NPC. [11][12][13][14][15] However, the antitumor activity of anti-EGFR mAbs for RM-NPC has rarely been reported. 16,17 The aim of the present study was to evaluate the antitumor efficacy and safety of anti-EGFR mAbs (CTX or NTZ) plus palliative chemotherapy as a first-line treatment for RM-NPC.…”
Section: Introductionmentioning
confidence: 99%
“…However, what are the effects of anti-EGFR mAbs when incorporated into the induction or adjuvant phase? Peng et al 54 conducted a retrospective analysis suggesting that anti-EGFR mAbs in combination with IC may be a more effective and promising strategy for patients with locoregionally advanced NPC. Further investigations are required to explore the application of anti-EGFR mAbs in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of EGRF significantly increases the risk of adverse prognosis of NPC OS (HR = 1.86, 95%CI 1.25–2.77; P = 0.000),disease-free survival (DFS) (HR = 2.25, 95%CI 1.66–3.04; P = 0.000), locoregional recurrence free survival (LRFS) (HR = 2.93, 95%CI 1.71–5.02; P = 0.000) [15]. In patients with locally advanced NPC receiving IMRT, combined anti-EGFR receptor therapy may be a more effective treatment strategy [18].…”
Section: Introductionmentioning
confidence: 99%